Influence of Environment Factors on the Activities of Higher Education Institutions - Pliashko Olga S.; Lybak Iryna A. (Bìznes Inform, 2019)
The article carries out a study on the influence of environment factors on the activities of higher education institutions. Based on the analysis of statistics, it is determined that the formed external environment does not contribute to their full-fledged development. The political, socio-cultural, economic and technological factors of influence of the external environment on the activities of higher education institutions are allocated. It is determined that the main modern features of the development of national education are: decrease in the number of educational institutions; increase in the number of aided persons; demographic processes of decline of population and student-age residents; increase in the number of unemployed with higher education; external labor migration; low level of financing this economy sector, both at the expense of the budget and at the expense of the population; reducing the scientific and innovation activity of higher education institutions; reducing the attractiveness of Ukrainian institutions of higher education for foreign students.